2017
DOI: 10.3390/8100252
|View full text |Cite
|
Sign up to set email alerts
|

Network-Based Method for Identifying Co-Regeneration Genes in Bone, Dentin, Nerve and Vessel Tissues

Abstract: Bone and dental diseases are serious public health problems. Most current clinical treatments for these diseases can produce side effects. Regeneration is a promising therapy for bone and dental diseases, yielding natural tissue recovery with few side effects. Because soft tissues inside the bone and dentin are densely populated with nerves and vessels, the study of bone and dentin regeneration should also consider the co-regeneration of nerves and vessels. In this study, a network-based method to identify co-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“… 17 The RANK/RANKL/OPG signalling pathway is triggered in MRONJ subjects. 19 A recent study demonstrated that zoledronate can enhance osteoclastogenesis through elevated expression of interleukin-6 (IL-6), followed by activation of the STAT3 pathway, which is related to vessel regeneration around bone tissues, 20 and finally the expression of RANKL. 21 Denosumab, a recently developed antiresorptive medication, is an anti-RANKL antibody that utilises the same mechanism of action as OPG.…”
Section: Pathogenesis and Risk Factors Of Mronjmentioning
confidence: 99%
“… 17 The RANK/RANKL/OPG signalling pathway is triggered in MRONJ subjects. 19 A recent study demonstrated that zoledronate can enhance osteoclastogenesis through elevated expression of interleukin-6 (IL-6), followed by activation of the STAT3 pathway, which is related to vessel regeneration around bone tissues, 20 and finally the expression of RANKL. 21 Denosumab, a recently developed antiresorptive medication, is an anti-RANKL antibody that utilises the same mechanism of action as OPG.…”
Section: Pathogenesis and Risk Factors Of Mronjmentioning
confidence: 99%